Reconciliation responses, blame, and expressions of guilt or shame. (21st May 2013) - Kamau, Caroline; Giner‐Sorolla, Roger; Zebel, Sven
Abstract: Recipients of intergroup apologies have been found to prefer expressions of shame over guilt. However, there is little research comparing the responses of a wronged group with those of a blamed group. Kenyans/Britons evaluated guilt/shame statements about colonialism, with blame measured as the assignment of collective guilt to Britain. Among Britons, there was a significant interaction, with high in‐group blamers expecting more reconciliation from shame than from guilt, and vice versa for low in‐group blamers. Among Kenyans, there was no main effect of blame, but more reconciliation was expected from shame than from guilt. Wronged groups thus appear to prefer shame over guilt, whereas preference for guilt/shame among members of a blamed group depends on the level of in‐group blame.